A Conceptual Framework for Maintenance Decision-Making in a Defense System Based on Operational Readiness and Industrial Capacity - Firdah Dipi Juni Kurniawati; G. Royke Deksino; I.B. Putra Jandhana; Ade Muhammad; Sri Yanto; Sulfi Indriani (International Journal of Education, Vocational and Social Science, 2026)
This study develops a conceptual framework for maintenance decision-making in the defense sector by considering two key dimensions, namely operational readiness and industrial capacity. In practice, decision-making related to maintenance in complex systems is influenced not only by technical aspects but also by various supporting factors, such as system reliability, spare parts availability, logistics readiness, human resource competence, industrial support, technological capability, maintenance costs, and supply chain capability. However, current approaches often have a limited scope and are insufficient in capturing the interdependencies among these factors. To address these limitations, this study proposes a framework based on Multi-Criteria Decision Making (MCDM) using the Fuzzy Analytic Hierarchy Process (FAHP). This approach was chosen because it can handle uncertainty and subjectivity in criterion assessment. The developed framework is expected to serve as a basis for establishing maintenance decision-making priorities in a more systematic manner and to provide direction for future empirical research.